Deep-Sea Exploration: A Bibliometric Analysis - Judijanto, Loso (West Science Interdisciplinary Studies, 2025)
Deep-sea exploration represents one of the most dynamic frontiers in contemporary science, integrating oceanography, marine engineering, ecology, and resource management. This study conducts a bibliometric analysis to systematically evaluate the evolution, thematic structure, and collaboration networks within deep-sea exploration research between 1980 and 2025. Using the Scopus database and VOSviewer for analysis and visualization, the study identifies major research trends, key contributing countries and institutions, and emerging areas of innovation. The results indicate a clear shift from traditional oceanographic studies and environmental assessments toward technologically driven themes, such as autonomous underwater vehicles (AUVs), remotely operated vehicles (ROVs), robotics, and underwater imaging. International collaboration patterns reveal China, the United States, and Japan as central players, supported by extensive networks with European and Asian partners. Furthermore, the co-occurrence of industrial themes such as offshore oil production and underwater mineral resources reflects the growing intersection between scientific discovery and commercial applications. The study contributes to theoretical discussions on knowledge evolution and interdisciplinarity while offering practical implications for policymakers, funding agencies, and industry stakeholders to foster sustainable and collaborative approaches in deep-sea exploration. Limitations regarding database coverage and emerging theme visibility are acknowledged, with recommendations for future research employing mixed-method strategies.